The Correlation of Perception About Online Learning With Anxiety Levels In The Internship Program at School of Nursing Jember University - Riski Hidayaturrohkim; Emi Wuri Wuryaningsih; Fitrio Deviantony (KHD-Production, 2022)
The COVID-19 pandemic has turned virtually all learning activities into online. Stressors experienced during online learning affect the psychological condition of internship nursing students. This research analyzes the correlation between perception about online learning with anxiety levels in the internship program at the school of Nursing Jember University. The method of this Research used an observational analytic with a cross-sectional approach. Respondents in this study were 102 internship nursing students who have had a minimum of two weeks of an online learning experience and using the total sampling technique. The study was conducted through an online survey. Bivariate analysis was performed by Kendal tau b correlation test (p=0,05). The research instrument of perception online learning questionnaire (α Cronbach = 0.847-0.867) and Zung Self Rating Anxiety Scale (α cronbach= 0.887). The Research has passed the research feasibility through the Health Research Ethics Commission the Faculty of Nursing, University of Jember No. 26/UN25.1.14/KEPK/2021. The results showed a total of 55 internship nursing students (53,9%) had a pretty good perception about online learning and (90,2%) stated that a mild level of anxiety. Moreover, there was no relation between perception about online learning with anxiety levels (p>0,05). Experience and knowledge become one factor that influences student perceptions—fairly good perception related to positive feelings to minimize anxiety. Besides that, internship nursing students have a good self-adaptation to the online learning transition period to not relate to anxiety. Further researchers can identify risk factors for causing anxiety in students.